CGRP Regulates the Age-Related Switch Between Osteoblast and Adipocyte Differentiation - Li, Hang; Qu, Jian; Zhu, Haihong; Wang, Jiaojiao; He, Hao; Xie, Xinyan; Wu, Ren; Lu, Qiong (Frontiers in Cell and Developmental Biology, 2021)
Osteoporosis is a chronic age-related disease. During aging, bone marrow-derived mesenchymal stem cells (BMSCs) display increased adipogenic, along with decreased osteogenic, differentiation capacity. The aim of the present study was to investigate the effect of calcitonin gene-related peptide (CGRP) on the osteogenic and adipogenic differentiation potential of BMSC-derived osteoblasts. Here, we found that the level of CGRP was markedly lower in bone marrow supernatant from aged mice compared with that in young mice. In vitro experiments indicated that CGRP promoted the osteogenic differentiation of BMSCs while inhibiting their adipogenic differentiation. Compared with vehicle-treated controls, aged mice treated with CGRP showed a substantial promotion of bone formation and a reduction in fat accumulation in the bone marrow. Similarly, we found that CGRP could significantly enhance bone formation in ovariectomized (OVX)mice in vivo. Together, our results suggested that CGRP may be a key regulator of the age-related switch between osteogenesis and adipogenesis in BMSCs and may represent a potential therapeutic strategy for the treatment of age-related bone loss.